The Effectiveness of Novel Growth Regulator and Fertilizer to Improve Quality and Yield of Spring Wheat - Shimendi G. Okbagabir; Mohammed H. Al-Mamoori; Elena N. Pakina; Meysamr Zargar (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
Reducing the use of chemical fertilizers is possible by implementing environmentally friendly smart farming technology like growth regulators and foliar fertilizer interactions. The experiment was entitled “Effectiveness of novel growth regulator and fertilizer to improve spring wheat quality and yield production.” The field was conducted at Barybino, Moscow Region in 2023. The experiment comprised 16 treatment combinations in Randomized Complete Block Design (RCBD) viz plant growth regulators (PGR) Centrino-1 (GR1), Centrino-2 (GR2), Centrino-3 (GR3), and Terrasay Fertilizer-1 (F1), Terrasay Fertilizer-2 (F2) and Terrasay-3 (F3) and Control (Co).  The purpose of the research work was, to examine the effects of a new formulation of foliar fertilizer and PGR on the quality and productivity of spring wheat, and to determine the best way and right dosage levels of growth regulators and fertilizers to increase crop resistance, nutrient uptake efficiency of the crop. The results showed GR3F2 need-based led to the highest plant height (69.8cm) and leaf area (7.63 cm2). GR2F1 attained the highest number of tillers, root length, biological yield, grain yield, and gluten with a mean value of 3 tiller plant-1, 10.7cm, 11118 kg ha-1, 5042kg ha-1 and 12.30 respectively. GR1F3 and GR2F2 recorded the highest in protein, and carbohydrate with a mean value of 9.63%, and 89% respectively. In conclusion, proficient handling of plant growth regulators (PGR) and fertilizers (F) can be considered as a crop management strategy to boost yield and quality by improving chemical fertilization, utilization efficiency, and reducing environmental pollution.